The Professional Values of Nursing Students - Sovia; Ani Haryani; Eka Ernawati; Lukmanulhakim (Health and Technology Journal (HTechJ), 2024)
Nursing professional values ​​are very important, especially when interacting with patients, directing them to behave according to professional values ​​in providing nursing care to create professional behavior. The process of learning professional values ​​begins when students are in the educational process. The purpose of the study was to describe the professional values ​​of nursing students in the nursing academic and internship program at the University of Faletehan. This type of research is descriptive with a cross-sectional approach, the sampling technique uses total sampling with 241 students as respondents. Data were collected using the NPVS-3 (Nurses Professional Values ​​Scale-3) questionnaire. The validity and reliability of the Indonesian version of the NPVS-3 questionnaire have been obtained from previous research with a Cronbach alpha value of 0.959. The results showed that most of the respondents (54.4%) rated their professional values ​​in the low category. Based on the sub-variables, caring is a sub-variable that is considered low by most of the respondents (56.0%). Professionalism was also rated low by most of the respondents (55.2%). In contrast to the other two sub-variables in the activism sub-variable, most of the respondents rated it in the high category (51.9%). The results of this study can be used as an evaluation by educational institutions so that they can further develop a curriculum that supports the improvement of the professional values ​​of nursing students and can be used as a reference in the preparation of future learning strategies.